2017
DOI: 10.1053/j.sodo.2017.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Heredity, genetics and orthodontics: How much has this research really helped?

Abstract: Uncovering the genetic factors that correlate with a clinical deviation of previously unknown etiology helps to diminish the unknown variation influencing the phenotype. Clinical studies, particularly those that consider the effects of an appliance or treatment regimen on growth, need to be a part of these types of genetic investigations in the future. While the day-to-day utilization of “testing” for genetic factors is not ready for practice yet, genetic testing for monogenic traits such as Primary Failure of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 88 publications
0
11
0
2
Order By: Relevance
“…The genetic factors appear to be heterogeneous with monogenic influence (usually autosomal dominant with incomplete penetrance and variable expressivity) in some families and multifactorial (polygenic complex) influence in others. 6 …”
Section: Genetic Influence On Skeletal Relationship Of Jawsmentioning
confidence: 99%
“…The genetic factors appear to be heterogeneous with monogenic influence (usually autosomal dominant with incomplete penetrance and variable expressivity) in some families and multifactorial (polygenic complex) influence in others. 6 …”
Section: Genetic Influence On Skeletal Relationship Of Jawsmentioning
confidence: 99%
“…In addition, there are also skeletal muscle proteins such as α-actin-2 and α-actin-3 (fast twitch fiber or type II). Studies have shown that an increased vertical dimension is inversely related to type II muscle fibers, that is, anterior open bite or increased vertical dimension is associated with type I muscle fibers (of slow contraction) that can be found in the masseter muscle [82].…”
Section: Genes Involved In the Development Of Soft Tissuesmentioning
confidence: 99%
“…Reference [82] observed a significant difference in the growth of the mandible in the sagittal plane, when they compared groups of Caucasian men with a genetic variation in the CYP19A1 gene with groups of women who inherited the same genetic variation. It was observed that the group of men showed more significant differences in facial growth than the group of women, suggesting that the variant of the CYP19A1 gene may be a multiethnic marker for the sagittal growth of the male mandible.…”
Section: Genes Involved In Facial Bone Growthmentioning
confidence: 99%
See 1 more Smart Citation
“…Hartsfield et al (2017), relata que os fatores genéticos determinam os diferentes fenótipos, mas que esses fatores se relacionam ou impactam com os fatores ambientais, incluindo o tratamento ortodôntico. O mais importante "teste genético" que o praticante pode fazer hoje é reunir a história individual e familiar do paciente.…”
unclassified